Steroid Receptor Coactivator-1 from Brain Physically Interacts Differentially with Steroid Receptor Subtypes - Molenda-Figueira, Heather A. (The Endocrine Society, 2008)
In vitro studies reveal that nuclear receptor coactivators enhance the transcriptional activity of steroid receptors, including estrogen (ER) and progestin receptors (PR), through ligand-dependent interactions. Whereas work from our laboratory and others shows that steroid receptor coactivator-1 (SRC-1) is essential for efficient ER and PR action in brain, very little is known about receptor-coactivator interactions in brain. In the present studies, pull-down assays were used to test the hypotheses that SRC-1 from hypothalamic and hippocampal tissue physically associate with recombinant PR or ER in a ligand-dependent manner. SRC-1, from hypothalamus or hippocampus, interacted with PR-A and PR-B in the presence of an agonist, but not in the absence of ligand or in the presence of a selective PR modulator, RU486. Interestingly, SRC-1 from brain associated more with PR-B, the stronger transcriptional activator, than with PR-A. In addition, SRC-1 from brain, which was confirmed by mass spectrometry, interacted with ERα and ERβ in the presence of agonist but not when unliganded or in the presence of the selective ER modulator, tamoxifen. Furthermore, SRC-1 from hypothalamus, but not hippocampus, interacted more with ERα than ERβ, suggesting distinct expression patterns of other cofactors in these brain regions. These findings suggest that interactions of SRC-1 from brain with PR and ER are dependent on ligand, receptor subtype, and brain region to manifest the pleiotropic functional consequences that underlie steroid-regulated behaviors. The present findings reveal distinct contrasts with previous cell culture studies and emphasize the importance of studying receptor-coactivator interactions using biologically relevant tissue.